Web-Based Waste Reporting Application Programming in Kampar District - Fadhil, Ahmad; Gusman, Deddy; Setiawan, Beni (Journal of Engineering Science and Technology Management (JES-TM), 2022)
Garbage is one of the social problems faced by society. Garbage can have a negative impact on health if not handled. If the waste is disposed of carelessly, it will cause various health problems in the community. Thus, a more effective way is needed to improve communication between the community and the government regarding waste reporting. Currently, the handling of waste in Kampar Regency is the responsibility of the Environmental Service (DLH). Therefore, a web-based waste reporting application will be made using the PHP programming language and the MYSQL database. The methodology used in designing this system is using the RUP method. The advantage in this website-based waste reporting application is that it can make it easier for the public to report waste. In addition, the Environmental Service of Kampar Regency can find out the locations of piles of garbage reported by the community.